The direct and indirect effect of neuroticism on work engagement of nurses during COVID-19: A temporal analysis - Vachhrajani, Mit; Mishra, Sushanta Kumar; Rai, Himanshu; Paliwal, Amit (Frontiers in Psychology, 2022)
Healthcare professionals such as nurses faced a tough time during the pandemic. Despite the personal and professional challenges, they contributed immensely during the pandemic. However, there were variations in nurses’ work engagement during the pandemic. One reason could be their personality, especially neuroticism. Neuroticism represents individuals’ proneness to distress in stressful situations, such as COVID-19. Hence, understanding how and in which conditions neuroticism influences work engagement is crucial. We used the Job Demand-Resource (JD-R) model to test the association between neuroticism and work engagement. As neuroticism represents the stress-proneness of an individual, we further investigated if stress mediates the neuroticism-work engagement link. For the nurses, patient interaction is an integral part of their job. Based on the data collected from the nurses, we tested if contact with patients (i.e., beneficiary contact) alleviates the adverse effect of neuroticism on work engagement. During COVID-19, there was an intense need for nursing support. Hence, avoiding duty when society is looking for support might induce a fear of stigmatization among the nurses. We examined if the perceived stigma of duty avoidance would affect the neuroticism-engagement relationship. Our results indicated that higher patient contact alleviated the adverse effect of neuroticism on work engagement. On the other hand, higher fear of stigma exacerbated the adverse effect of neuroticism on work engagement. We further checked the combined effect of beneficiary contact and fear of stigma on neuroticism-work engagement relationships. The findings highlighted the importance of societal factors and policymakers in enhancing nurses’ work engagement.